Cystatin C: A Promising Marker of Renal Function in Patients with Systemic Lupus Erythematosus? - Peixoto, Lígia; Aguiar, Patrício; Bragança, Raquel de; Martins, Joana Rosa; Acabado, Alba Janeiro; Ducla-Sores, José Luís (Acta Médica Portuguesa, 2015)
Purpose: Cystatin C has a higher correlation with glomerular filtration rate and a more significant clinical prognosis than creatinine. We sought to determine whether it is a marker of renal function different from creatinine (cystatin C potentially superior to creatinine), in patients with systemic lupus erythematosus. Material and Methods: 37 patients with systemic lupus erythematosus were evaluated. Serum cystatin C was determined by nephelometry and creatinine by modified Jaffe method. We compared five formulas: Chronic Kidney Disease – Epidemiology Collaboration cystiatin; Chronic Kidney Disease – Epidemiology Collaboration creatinine-cystatin; Cockcroft-Gault; Modification of Diet in Renal Disease and Chronic Kidney Disease – Epidemiology Collaboration creatinine, using the latter as a reference. We analyzed the influence of clinical and laboratory factors in cystatin C variation, using multivariate linear regression. Results: Cystatin C was singly elevated in ten participants, versus none isolated creatinine elevation, and this difference was significant (p = 0.002). There was a difference between the estimated glomerular filtration rate by Chronic Kidney Disease – Epidemiology Collaboration cystatin and by Chronic Kidney Disease – Epidemiology Collaboration creatinine (-6.0541 mL/min/1.73 m2, p = 0.07), more pronounced for lower glomerular filtration rate. Consequently, Chronic Kidney Disease – Epidemiology Collaboration cystatin reclassified 4 patients as having chronic kidney disease de novo and 1 patient as not having chronic kidney disease (p = 0.375). Cystatin C was only significantly influenced by age (p < 0.001). Discussion: Several reports showed cystatin C as a better marker to define chronic kidney disease, allowing more accurate classification and risk stratification, compared with creatinine. In this study, Cystatin C revealed as a promisor marker of renal function in patient with lupus, mainly in patients with lower glomerular filtration rates. The correlation between age and cystatin C seems to be a confounding factor, as glomerular filtration rate physiologically declines with ageing. Conclusion: Cystatin C was potentially superior to creatinine and in this study and cystatin C seems to detect changes in glomerular filtration rate earlier than creatinine and may be a better screening method for chronic kidney disease in systemic lupus erythematosus.